Olivocerebellar modulation of motor cortex ability to generate vibrissal movements in rat - Lang, Eric J (Blackwell Science Inc, 2006)
The vibrissal movements known as whisking are generated in a pulsatile, or non-continuous, fashion and comprise sequences of brief regularly spaced movements. These rhythmic timing sequences imply the existence of periodically issued motor commands. As inferior olivary (IO) neurones generate periodic synchronous discharges that could provide the underlying timing signal, this possibility was tested by determining whether the olivocerebellar system modulates motor cortex (MCtx)-triggered whisker movements in rats. Trains of current pulses were applied to MCtx, and the resulting whisker movements were recorded using a high speed video camera. The evoked movement patterns demonstrated properties consistent with the existence of an oscillatory motor driving rhythm. In particular, movement amplitude showed a bell-shaped dependence on stimulus frequency, with a peak at 11.5 ± 2.3 Hz. Moreover, movement trajectories showed harmonic and subharmonic entrainment patterns within specific stimulus frequency ranges. By contrast, movements evoked by facial nerve stimulation showed no such frequency-dependent properties. To test whether the IO was the oscillator in question, IO neuronal properties were modified in vivo by intra-IO picrotoxin injection, which enhances synchronous oscillatory IO activity and reduces its natural frequency. The ensuing changes in the evoked whisker patterns were consistent with these pharmacological effects. Furthermore, in cerebellectomized rats, oscillatory modulation of MCtx-evoked movements was greatly reduced, and intra-IO picrotoxin injections did not affect the evoked movement patterns. Additionally, multielectrode recording of Purkinje cell complex spikes showed a temporal correlation of olivocerebellar activity during MCtx stimulus trains to evoked movement patterns. In sum, the results indicate that MCtx's ability to generate movements is modulated by an oscillatory signal arising in the olivocerebellar system.